Padlet sebagai Media Pembelajaran Teks Kritik Sastra dan Esai di SMAN 9 Semarang - Fajar Fitra Dewi; Asep Purwo Yudi Utomo; Tetti Kusuma Widyawati; Daniyar Rohman; Didi Pramono; Rossi Galih Kesuma; Nico Satya Yunanda (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
21st century education is a learning that is carried out by integrating and utilizing the avaibility of technology in learning activities. One of the learning innovations that can be implemented by integrating technology is learning media. Padlet is a platform that can be an application or a web that allows its users to share text, photos, links or other content and comment on each other. This paper aims to describe the use of padlets as a learning media for teks kritik sastra dan esai. This research method is a qualitative descriptive method that describe the use of padlets as a learning medium for teks kritik sastra dan esai. Data collection analysis techniques in this study were through observation steps and through student opinion questionnaires. The results of data collection show that students enjoy and helped by learning to use padlet media. From these results, it can be conclude that this study shows padlets can be used as learning media that can answer the demands of 21st century learning and help students in learning activities on teks kritik sastra dan esai.